Phonological Accent Preferences and Learning Patterns among EFL Learners - Yanti, Alya Dwi; Putri, Khairina Melani; Sitanggang, Juni Artha; Malau, Nova Anggriyani; Sinurat, Bloner (Innovative: Journal Of Social Science Research, 2025)
This research examines English language learning patterns and EFL students' pronunciation preferences for British and American accents. This research analyzes students' phonological preferences through formal and informal learning activities with the ultimate goal of improving English teaching methods. Data were collected through questionnaires and audio recordings. Closed-ended and The participants of this research consisted of 10 high school students from various schools in Pematangsiantar, North Sumatra, were selected through purposive sampling. open-ended questions were asked about students' English learning backgrounds, use of English-language media, and their opinions on accents. Audio recordings of students reading the narrative text "A Surprising Morning" were used to collect pronunciation data. The text included 15 of the most common words in British and American accents. In the phonological research of 150 pronunciations (10 students × 15 words), 80 (53.3%) preferred the American accent, while 70 (46.6%) preferred the British accent. Students were more likely to pronounce with an American accent, although the difference was not significant. According to the questionnaire, more students watched American English films, songs, and social media than British media. This research shows that media-influenced learning patterns increase students' phonological preference for the American accent. To improve students' phonological awareness, teachers should clearly explain accent differences in class and use diverse learning resources.